Digital Transformation of Teacher Education by Bridging Digital Divide between Teacher Educators and Prospective Teachers - Aysha Khalil, Nasim Ishaq & Andayani Boedihartono (JCTE, 2023)
Digitalization has profoundly transformed the organizational processes, activities, experiences and teaching-learning models to fully persuade the shifts and prospects of a blend of digital technologies and their elevating effects across whole education sector in an ordered, strategic and highlighted way. Teacher education is highly influenced by the digital transformation globally. In Pakistan, it is imperative to digitally transform teacher education so that by overcoming the current prevailing challenges. Digital divide is one of the biggest challenges predominated in teacher education which necessitates to be bridged for meeting learning needs of prospective teachers. This research study was conducted to analyze the need and ways to bring digital transformation in teacher education by bridging the digital divide between teacher educators and prospective teaches. The study was descriptive in nature which followed quantitative method whereas sample of this study comprised of prospective teachers and teacher educators from education departments of three universities of Lahore. The study revealed that there is a dire need to bring digital transformation in teacher education, while there exists a prominent digital divide where prospective teachers are comparatively more superior in digital competencies and digital literacy. It was also found that digital transformation and digital divide are closely related and occurrence of digital transformation is dependent upon applying strategies to bridge digital divide. The study suggests that if teacher education institutions employ some digital divide-bridging strategies like e-Training, digitization of curriculum, enhancing digital infrastructure and devising digital strategies, it is possible to beget digital transformation in teacher education.